Effect of graphene nanoplatelets addition on the elastic properties of short ceramic fiber-reinforced aluminum-based hybrid nanocomposites. Issue 4 (3rd April 2022) - Zhang, Dangquan; Ashraf, Muhammad Aqeel; Liu, Zhenling; Li, Cheng; Peng, Wanxi
Abstract: Effects of adding graphene nanoplatelets (GNPs) on the elastic properties of short SiC fiber-reinforced aluminum (Al)-based hybrid nanocomposites are evaluated using a micromechanical approach. Agglomeration and size of GNPs and formation of Al/GNP Al4C3 interphase are evaluated. Influences of alignment, aspect ratio and volume fraction of SiC on the Al-based hybrid nanocomposite properties are studied. Addition of the GNPs results in improved elastic modulus of the hybrid nanocomposites. The elastic modulus appears to increase by (i) increasing GNP length, (ii) decreasing the GNP thickness and (iii) generating Al4C3 layer. The GNP agglomeration reduces the hybrid nanocomposite mechanical performances.